Strategi Cooperative Reading Circles Dalam Mengatasi Kesulitan Membaca Al-Qur’an Pada Siswa SMPN 5 Tuban - Izzatul Firdaus (Yayasan Al-Afif, 2025)
The difficulty in reading the Qur'an among students at SMPN 5 Tuban is a serious challenge that impacts both the academic aspects of Islamic Religious Education (PAI) and the development of students' religious character. This problem stems from low student motivation and enthusiasm for learning, combined with minimal support and guidance from parents. This study aims to identify the main factors causing difficulties in reading the Qur'an and to analyze the effectiveness of implementing the Cooperative Reading Circles (CRC) Learning Model as a strategy to overcome this issue. This field research uses a descriptive qualitative approach , with the research subjects being students of class 9F and the PAI teacher at SMPN 5 Tuban. Data collection was carried out through observation, interviews, and documentation. The results show that CRC implementation proved effective by creating a collaborative learning environment and leveraging the role of peer tutors (Mumtaz students) for direct correction of makharijul huruf and tajwid accuracy. Students with the greatest difficulty (Kaffah) received intensive, direct guidance from the teacher using the An-Nahdiyah Method. This strategy significantly increased students' accuracy, fluency, motivation, and confidence. In conclusion, CRC, combined with the An-Nahdiyah Method, is a systematic solution to improve basic Qur'an Tahsin skills while fostering students' learning spirit and social responsibility. Keywords: Cooperative Reading Circles, Difficulty in Reading, Strategy